Digital health economics education: perspectives, potential and barriers at German medical universities - Hertling, Stefan; Schöffski, Oliver; Graul, Isabel; Schleußner, Ekkehard (Frontiers in Medicine, 2025)
BackgroundThe increasing economization of healthcare systems highlights the need to integrate health economics more systematically into medical education.ObjectiveThis study examines the perspectives of deans of German medical faculties on the integration of health economics content into medical studies. It also focuses on determining their ideas about suitable teaching formats and identifying potential obstacles to implementation. A particular and paradoxical finding of the study is the unanimous rejection of digital teaching formats by all participating faculties.Materials and methodsThe pilot cross-sectional survey was conducted between April and October 2021. Deans and academic representatives from all 36 medical faculties in Germany were invited to participate. Data was collected using two specially developed standardized questionnaires with 24 questions.ResultsA total of 28 medical faculties participated in the survey. 88% of respondents do not currently teach health economics, although 92% consider teaching health economics in medical studies to be important. The main obstacles cited are the lack of recognition as a medical discipline (96%), the absence of a conceptual curriculum (77%) and a lack of teaching capacity and financial resources (77 and 62% respectively). 81% see a conceptual curriculum as a prerequisite for national standardization. 38% call for interdisciplinary cooperation with health economics faculties.